2021
DOI: 10.3174/ajnr.a7203
|View full text |Cite
|
Sign up to set email alerts
|

The Safety of Intra-arterial Tirofiban during Endovascular Therapy after Intravenous Thrombolysis

Abstract: BACKGROUND AND PURPOSE:The safety and efficacy of tirofiban during endovascular therapy in patients undergoing intravenous thrombolysis with recombinant IV tPA remain unclear. This study aimed to investigate the safety and efficacy of intra-arterial tirofiban use during endovascular therapy in patients treated with IV tPA. MATERIALS AND METHODS:Using a multicenter registry, we enrolled patients with acute ischemic stroke who underwent endovascular therapy. Safety outcomes included postprocedural parenchymal he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 39 publications
(38 reference statements)
1
22
0
Order By: Relevance
“…A search from databases identified 329 papers (Pubmed:40, EMBASE: 83, The Cochrane Library: 25, Web of Science: 105, CNKI 46, Wanfang: 30), of which 62 duplicates were excluded, the titles and abstracts of the shortlisted papers were reviewed and another 247 papers, and the remaining 20 papers were read in full-text detail to determine whether they met the inclusion/exclusion criteria, and ultimately, 7 eligible (16)(17)(18)(19)(20)(21)(22) papers were included in this meta-analysis (shown in Figure 1).…”
Section: Search Results and Selection Of Research Subjectsmentioning
confidence: 99%
See 3 more Smart Citations
“…A search from databases identified 329 papers (Pubmed:40, EMBASE: 83, The Cochrane Library: 25, Web of Science: 105, CNKI 46, Wanfang: 30), of which 62 duplicates were excluded, the titles and abstracts of the shortlisted papers were reviewed and another 247 papers, and the remaining 20 papers were read in full-text detail to determine whether they met the inclusion/exclusion criteria, and ultimately, 7 eligible (16)(17)(18)(19)(20)(21)(22) papers were included in this meta-analysis (shown in Figure 1).…”
Section: Search Results and Selection Of Research Subjectsmentioning
confidence: 99%
“…One thousand one hundred and seventy six patients from seven (16)(17)(18)(19)(20)(21)(22) studies [one (22) randomized controlled trial and six (16)(17)(18)(19)(20)(21) observational studies] were included in the final analysis, of which 340 patients (28.9%) were treated with tirofiban. Basic characteristics of the included studies are shown in Table 1.…”
Section: Basic Characteristics Of the Research Objectmentioning
confidence: 99%
See 2 more Smart Citations
“…Accurate prediction of perfusion outcome may help in the selection of patients for e.g. intra-arterial thrombolysis [35,36] administration of antithrombotics [37,38] or secondary distal MT [39,40]. While potentially beneficial, all of these treatments also harbor a risk of harm, warranting a careful patient selection.…”
Section: Potential Role Of Ivt As Rescue Treatmentmentioning
confidence: 99%